O-031 Catheter tip shape optimization using a parameterized model of the simmons catheter. (23rd July 2022) - Zerebiec, K; Boyle, J; Silveira, L; Muse, J; Kreuser, G; Paris, T; Floreani, R; Johnson, D; Raymond, S
Abstract : Introduction/Purpose: Many practitioners have transitioned from transfemoral to a radial first approach for cerebral angiography due to the improved safety profile and patient satisfaction. The Simmons 2 catheter is the most commonly used and is adequate but not optimized for transradial cerebral angiography. In this study, we built a library of reverse curve catheter shapes based on variations in the Simmons 2 design and tested library performance in a silicone transradial aortic arch model. Materials and Methods: The reverse curve shape is defined by 9 parameters that describe three curves and adjacent segments ( figure 1 ): the three angles (A1–3), the radius of curvature at each of the angles (R1–3) and the segment lengths (D1–3). For the classic Simmons 2 shape, A1 is 180 degrees, A2 is 15 degrees and A3 is approximately 245 degrees. We designed shaping forms with varying A1 (180, 210, and 240 degrees, figure 2 ) using the parameterized model in Onshape, a browser-based computer aided design platform, to draw plates with 5 Fr width grooves following the desired catheter tip shape. These shaping forms were then produced in aluminum by CNC-milling (Xometry). The straight 5 Fr Terumo GLIDECATH was used as a stock catheter and shaped by heating the catheter in the form at 160 degrees Celsius for 15 minutes with immediate quenching in room temperature water. Catheter performance was evaluated with two tasks: catheter reforming at the arch (without a wire) and great vessel selection from the arch using a silicone transradial aortic arch model (Mentice). Three trainee operators performed 10 timed trials of each task with each catheter. Results: Catheter reformation at the arch was slightly faster for the 210 degree catheter but similar to slightly slower for the 240 degree catheter. Vessel selection was similar for all of the catheters with some variation between operators. Conclusions: Catheter tip shape affects performance of maneuvers including tip reformation at the arch and vessel selection. We demonstrated an approach for rapid tip shape prototyping and performance evaluation in a silicone arch model and used the approach to optimize one parameter in a model of the Simmons 2 catheter. Future work is needed to evaluate additional shape parameters. Disclosures: K. Zerebiec: None. J. Boyle: None. L. Silveira: None. J. Muse: None. G. Kreuser: None. T. Paris: None. R. Floreani: None. D. Johnson: None. S. Raymond: None.